2018
DOI: 10.1016/j.jbo.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and prognostic characteristics of bone metastases and skeletal-related events (SREs) in breast cancer patients: A systematic review of the real world data

Abstract: PurposeThe aim was to systematically extrapolate the occurrence, risk factors, prognostic characteristics, management and outcome of bone metastases (BM) and skeletal related events (SREs) of breast cancer survivors in the real world clinical setting.MethodsA systematic literature search of PubMed, Web of Science, EMBASE OvidSP and EBSCO Academic Search Complete was conducted. Published prospective and retrospective papers investigating BM and SREs in breast cancer patients in non-trial settings were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 60 publications
3
38
0
6
Order By: Relevance
“…Such early assessment of developing bone metastases would enable patient-specific bone-targeted treatment. However, treatment options for patients with bone metastases are scarce and palliative rather than curative 4,5 . Consequently, the design of novel theranostic compounds which detect and treat bone metastases in cancer patients would overcome this unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…Such early assessment of developing bone metastases would enable patient-specific bone-targeted treatment. However, treatment options for patients with bone metastases are scarce and palliative rather than curative 4,5 . Consequently, the design of novel theranostic compounds which detect and treat bone metastases in cancer patients would overcome this unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, cancers of the breast, prostate, and lung have a high propensity for metastasis to bone, with 73%, 68%, and 36% of patients with advanced cancer developing a bony lesion, respectively . Estrogen‐receptor positive status has been identified as a potential risk for developing breast cancer bone metastases; however, a recent systematic analysis concluded that the primary risk factors for developing bone metastases in women with breast cancer are younger age, greater stage, and larger tumor size at diagnosis, whereas estrogen‐receptor status had no effect on bone metastasis risk . For patients diagnosed with prostate cancer, PSA levels ≥20 ng/mL, a Gleason score ≥8, and locally advanced disease are risk factors for developing bone metastases .…”
Section: Introductionmentioning
confidence: 99%
“…Most of bone metastases of BC patients were osteolytic, which could cause skeletal‐related events (SREs) including bone destruction, pathological fractures, hypercalcemia, and spinal cord or nerve root compression . Once bone metastases were diagnosed, the overall survival of BC patients decreased dramatically and median life expectancy dropped to 2‐3 years . Current treatment options for BC bone metastases (BCBM) are seldom curative and are instead mostly palliative .…”
Section: Introductionmentioning
confidence: 99%